2019
DOI: 10.1177/2050312119849769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of visual impairment among school children in three primary schools of Sekela Woreda, Amhara regional state, north-west Ethiopia

Abstract: Background: Although there are limited studies, recent data are lacking to determine the prevalence of eye problems in Ethiopia accurately and there is no scientific evidence of such study in Sekela Woreda. The purpose of this study was to determine the prevalence of visual impairment among school children in Sekela Woreda, Ethiopia. Methods: The study design was a community-based analytical cross-sectional with a multi-stage cluster random sampling technique from Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
2
16
2
Order By: Relevance
“…Students aged greater than 25 years of age had 1.8 times higher odds of developing visual impairment compared with their counterpart. This is in agreement with the study done on school children in Ethiopia [ 49 ], and in Pakistan [ 46 ]. The possible reason for the increase in VI with age might be as age increases, there is an increase in environmental exposure and related changes in the sensitivity of the visual pathway [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Students aged greater than 25 years of age had 1.8 times higher odds of developing visual impairment compared with their counterpart. This is in agreement with the study done on school children in Ethiopia [ 49 ], and in Pakistan [ 46 ]. The possible reason for the increase in VI with age might be as age increases, there is an increase in environmental exposure and related changes in the sensitivity of the visual pathway [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…The possible reason for the increase in VI with age might be as age increases, there is an increase in environmental exposure and related changes in the sensitivity of the visual pathway [ 50 ]. These biological changes give rise to visual dysfunction of the eye and reduced visual acuity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study reports a much lower estimate as compared to what has been reported in school-based studies from other Asian and African countries. [ 30 31 32 33 34 35 36 37 37 ] However, estimates from Nigeria and Latin America are comparable (1.26% and 2.67%). [ 38 39 ] Although it is difficult to compare these studies due to the difference in inclusion criteria, one similarity that could be found between these studies and the present study is the trend in increasing VI prevalence with age.…”
Section: Discussionmentioning
confidence: 99%
“…In the current meta-analysis, a total of 96 101 participants were included to estimate the pooled prevalence of blindness in Ethiopia. The studies were conducted in the different parts of Ethiopia: Nationwide,7 36 Oromia Region,51 Amhara Region,16 48 49 52–60 Tigray Region,61 Southern Nation Nationalities Peoples Region (SNNPR),62–66 Gambella and Benishangul Gumuz Regions,50 Addis Ababa City Administration8 67 68 and unspecified (ie, area) school-based study 47. All of the studies were published.…”
Section: Resultsmentioning
confidence: 99%